Pegylated liposomal doxorubicin in combination with mitomycin C, infusional 5-fluorouracil and sodium folinic acid. A phase-I-study in patients with upper gastrointestinal cancer - Hofheinz, Ralf-Dieter; Willer, Andreas; Weißer, Andreas; Gnad-Vogt, Ulrike; Saußele, Susanne; Kreil, Sebastian; Hartmann, Jörg Thomas; Hehlmann, Rüdiger; Hochhaus, Andreas (British journal of cancer, 2004)
Mitomycin C (MMC) in combination with infusional 5-fluorouracil (FU) plus folinic acid (FA) is an effective treatment for metastatic gastrointestinal cancer. Anthracyclines are commonly used in the treatment of upper gastrointestinal cancer. The aim of this study was to determine the maximum tolerated dose of liposomal, pegylated doxorubicin (Caelyx) in combination with infusional 5-FU/sodium FA and MMC. Escalating doses of Caelyx (15 - 25 - 30 - 35 mg m−2 corresponding to dose levels I-IV) were applied on days 1 and 29, given to fixed doses of 24-h 5-FU (2000 mg m−2) and sodium FA (500 mg m−2, mixed with 5-FU in one pump) weekly for 6 weeks, and MMC 7 mg m−2 on days 8 and 36. At least three patients were treated at each dose level. A total of 25 patients are evaluable. No dose-limiting toxicity (DLT) was observed on level I (n=3). On level II, DLT occurred in three out of five patients (mucositis and leucopenia). Owing to the early DLTs at this dose, we added a 20 mg m−2 Caelyx dose level (Ia). In total, 17 patients were treated at this dose level. Among these, only two patients experienced DLT in cycle one and 37 complete cycles have been administered in association with a low toxicity profile. The median dose intensity was 100% for each drug during the first course and no treatment delay exceeding 7 days was required. The recommended dose of 4-weekly Caelyx in combination with weekly 24-h 5-FU/sodium FA and 4-weekly MMC is 20 mg m−2. Preliminary antitumour activity has been observed in patients with pretreated pancreatic cancer and in untreated gastric cancer.
Gesehen am 13.05.2022